Clinical Significance of Composition and Functional Diversity of the Vaginal Microbiome in Recurrent Vaginitis - Kim, Min Jeong; Lee, Seungok; Kwon, Mi Yeon; Kim, Myungshin (Frontiers in Microbiology, 2022)
Objective The vaginal microbiome protects the female genital tract from various diseases, such as vaginitis, a vaginal inflammation characterized by abnormal discharge, itching, and pain. To evaluate the clinical relationship between the vaginal microbiome and the pathophysiology of recurrent vaginitis (RV), we investigated the microbiome taxonomic profile (MTP) in the vaginal samples of Korean female patients with RV. Methods Forty women of reproductive age diagnosed with RV were enrolled. The vaginal MTP of patients was analyzed using 16S ribosomal RNA gene sequencing, and the results were compared with that of healthy women (n = 100). Further, the association of the vaginal community state type (CST) with the clinical characteristics was analyzed. Results The species abundance of MTP was significantly lower in patients with RV than in healthy women (p < 0.05), whereas species evenness and diversity were significantly higher in patients with RV than in healthy individuals (p < 0.05). The proportion of the most common vaginal Lactobacillus spp. was significantly lower in the MTP of patients with RV than healthy women (p < 0.01). The beta diversity distance was also significantly different between patients with RV patients and healthy individuals (p = 0.001). Based on the CST, the MTP of 40 RV samples was categorized as follows: 21 (52.5%) for CST IV, 8 (20.0%) for CST III, 5 (12.5%) for CST I, 2 (5.0%) for CST II, 1 for (2.5%) for CST V, and 3 (7.5%) for mixed CST. Patients with underlying uterine diseases (uterine leiomyoma, adenomyosis, and endometrial polyps; n = 17) showed higher species richness and diversity than those without (n = 23; p < 0.05). Conclusion Changes in the species abundance and microbial diversity in the vagina were strongly associated with RV. A low proportion of Lactobacillus spp. was found in patients with RV than in healthy women. The abundance and diversity of bacterial taxa were significantly higher in patients with underlying gynecologic disease than those without. Our study offers an insight into the nature of the vaginal microbiome and proposes that surveying the vaginal microbiome is valuable for detecting and treating gynecologic diseases in the future.